2018
DOI: 10.1093/humrep/dey239
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic sorting selects sperm for clinical use with reduced DNA damage compared to density gradient centrifugation with swim-up in split semen samples

Abstract: No external funding to declare. Utkan Demirci, PhD is the Co-founder and Scientific Advisor for DxNow Inc., LevitasBio Inc. and Koek Biotech. Mitchell Rosen, MD is a member of the Clinical Advisory Board for DxNow Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
92
1
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(108 citation statements)
references
References 36 publications
12
92
1
3
Order By: Relevance
“…This was thought to be due to higher maternal age in Fertile group. The studies regarding the use of microfluidic chips for sperm sorting supported that these chips were able to sort spermatozoa with higher DNA integrity (Quinn et al, ; Schulte et al, ); these devices were introduced to ART market with the claim that their use might be beneficial for decreasing miscarriage rates which were reported to be affected by higher sperm DNA fragmentation (Carlini et al, ; Kumar et al, ). The results of our study showed no significant difference in miscarriage rates between both groups and did not support any advantage of chip over conventional sorting methods in terms of this outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was thought to be due to higher maternal age in Fertile group. The studies regarding the use of microfluidic chips for sperm sorting supported that these chips were able to sort spermatozoa with higher DNA integrity (Quinn et al, ; Schulte et al, ); these devices were introduced to ART market with the claim that their use might be beneficial for decreasing miscarriage rates which were reported to be affected by higher sperm DNA fragmentation (Carlini et al, ; Kumar et al, ). The results of our study showed no significant difference in miscarriage rates between both groups and did not support any advantage of chip over conventional sorting methods in terms of this outcome.…”
Section: Discussionmentioning
confidence: 99%
“…These systems have been integrated into use in the field of assisted reproduction after they were converged into systems that can be used with larger volume samples (Chinnasamy, Behr, & Demirci, ; Samuel et al, ). In addition, there are clinical studies showing that spermatozoa processed with these chips yielded higher DNA integrity and lower DNA damage compared with conventional sorting techniques (Quinn et al, ; Schulte, Chung, Ohl, Takayama, & Smith, ). However, the most important question whether their use is of any advantage in terms of laboratory and clinical IVF/ICSI outcomes still remains controversy.…”
Section: Introductionmentioning
confidence: 99%
“…Intracytoplasmic morphologically selected sperm injection (IMSI) uses high magnification to select the most morphologically normal sperm, as the presence of vacuoles in the nuclear region has been associated with high SDF [244,245]. Other approaches include the physiological intracytoplasmic sperm injection (PICSI), based on sperm binding to hyaluronic acid, and microfluidic devices, allowing sperm migration along microchannels [246][247][248][249].…”
Section: Sperm Processing and Preparationmentioning
confidence: 99%
“…Two of the most explored methods for sperm processing in ART-density gradient centrifugation (DGS) and swim-up (SU)-are investigated in details. Compared to fresh sample, the processed one has lower DNA fragmentation rates [134,135] and lower concentration of ROS regardless which method was used [136,137].…”
Section: Processing Sperm Samples In Vitromentioning
confidence: 99%